Staffing Study on the Impact of Changes to Severe Discipline Punishments After the Issue of Government Regulation Number 94 of 2021 Concerning Disciplinary Punishments for Civil Servants - Hartini, Sri; Kunarti, Siti; Kartono, Kartono; Haryanto, Tenang; Haryanto, Budiman Setyo (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The purpose of personnel analysis is to achieve professional civil servants in implementing the principles of good governance. To achieve this goal, one of the policies undertaken by the government is to issue a new regulation in the field of personnel as a substitute for the old regulation, namely Government Regulation No. 94 of 2021. The new policy issued by the government should be firmer, better and more effective. so that it will make Civil Servants who commit disciplinary violations become a deterrent. The new regulations have several changes to disciplinary penalties. One of the changes is severe disciplinary punishment. The old regulations set forth in PP No. 53 of 2010, regulated the existence of a penalty for dishonorable dismissal as civil servants, but in the replacement regulation this was omitted. By eliminating the word disrespect, it has an impact on the staffing sector, so that severe disciplinary punishment becomes lighter. The reduction in disciplinary punishment provides an opportunity for civil servants to commit repeated violations, thereby hampering the principles of good governance. In terms of staffing, these changes have an impact on civil servant pension rights. In this way, all civil servants who have been dismissed, both retired and for committing serious disciplinary violations, will receive pension rights. PP for PNS No. 94 of 2021 should carry out the Law's orders, but the new PP is not in line with Article 84 of the ASN Law.